2018
DOI: 10.3389/fsufs.2018.00053
|View full text |Cite
|
Sign up to set email alerts
|

Dual Use of a Biopolymer From Durian (Durio zibethinus) Seed as a Nutrient Source and Stabilizer for Spray Dried Lactobacillus Plantarum

Abstract: The search for natural and sustainable biopolymers is increasing. Biopolymers are used in applications, such as to encapsulate and stabilize probiotic bacteria. Currently, this process requires many steps, including the separation of bacteria from the culture media after fermentation, which is energy intensive. In this study, we developed a strategy to use a natural biopolymer from durian seed, durian seed gum (DSG), to address these issues. DSG was used to serve dual roles, firstly as a nutrient source, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…DSG exhibited highly hydrophilic character owing to the dominant presence of hydroxyl groups (-OH) contributed by the polysaccharides. The seed gum is not a galactomannan because it contains glucose, rhamnose and galactose in the ratio of 9:3:1 [24]. This nature of the molecular structure of monosaccharides also give rise to many polar hydroxyl groups (-OH) and carbonyl groups (C = O).…”
Section: Solubilitymentioning
confidence: 99%
“…DSG exhibited highly hydrophilic character owing to the dominant presence of hydroxyl groups (-OH) contributed by the polysaccharides. The seed gum is not a galactomannan because it contains glucose, rhamnose and galactose in the ratio of 9:3:1 [24]. This nature of the molecular structure of monosaccharides also give rise to many polar hydroxyl groups (-OH) and carbonyl groups (C = O).…”
Section: Solubilitymentioning
confidence: 99%
“…In Malaysia, among majority of the tropical fruit wastes which are generated and discarded in large quantities especially during special seasons are durian, jackfruit, Malaysian Longan and Tarap and date seeds. Studies by Akasha et al [10], Jaslyn et al [11], Noor Raihana et al [12], Fagundes et al [13] and Kleawkla et al [14] have demonstrated fruit seeds were found to contain significant amount of protein which can be utilized for various purposes including as natural coagulant in water treatment. According to Ndabigengesere et al [15], negatively charged particles bind with positively charged proteins via electrostatic interactions to form flocs and settle at the bottom of the water body.…”
Section: Introductionmentioning
confidence: 99%